If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -3 = 2 + 1x Reorder the terms: -3 + -4x = 2 + 1x Solving -3 + -4x = 2 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + -4x + -1x = 2 + 1x + -1x Combine like terms: -4x + -1x = -5x -3 + -5x = 2 + 1x + -1x Combine like terms: 1x + -1x = 0 -3 + -5x = 2 + 0 -3 + -5x = 2 Add '3' to each side of the equation. -3 + 3 + -5x = 2 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = 2 + 3 -5x = 2 + 3 Combine like terms: 2 + 3 = 5 -5x = 5 Divide each side by '-5'. x = -1 Simplifying x = -1
| 5x-(x-2)=2x-(3x+1) | | 7y=8x-14 | | 10+2x=180 | | 27x^2-48+5=0 | | 3x^3-15x^2-12x+180=0 | | 3c+7=5c-3 | | 566.38=230+1.21x | | 7r^2-20=8-45r | | -26.5=-9(5.5d+6) | | 6(2n-15)=120 | | 10--7= | | 0.25t+9=2 | | 2.5h-15=4hy | | 7r^2-29r=5+5r | | 5(z+6)=8 | | 2y+54+4y=6 | | 4x-8=2x-5 | | 0.7x+1.5=0.6x+2 | | 11x-6=10x+10 | | 8xy+3yz-9xz-8xy= | | 6=1b | | -62=8u-12u-18 | | 0.7x+1.5=0.6x+3 | | 32n^2+25n-10=-3n^2 | | -62=8u-12u+18 | | -4=-2(n+8) | | 56-(2c+4)=4(4+6)+c | | 10x^2-21x-27=0 | | 4(q-8)+q-3=5(q-7) | | Y=x^3-4+6 | | 56n^2+403n-282=-2-8n^2-5n | | 0.10(y-3)+0.14y=0.04y-0.05(30) |